Preventing kidney injury among sugarcane workers: promising evidence from enhanced workplace interventions. (13th May 2020) - Glaser, Jason; Hansson, Erik; Weiss, Ilana; Wesseling, Catharina; Jakobsson, Kristina; Ekström, Ulf; Apelqvist, Jenny; Lucas, Rebekah; Arias Monge, Esteban; Peraza, Sandra; Hogstedt, Christer; Wegman, David H
Abstract : Objectives: To assess if improvement of working conditions related to heat stress was associated with improved kidney health outcomes among sugarcane harvest workers in Chichigalpa, Nicaragua, a region heavily affected by the epidemic of chronic kidney disease of non-traditional origin. Methods: Based on our findings during the 2017–2018 harvest (harvest 1), recommendations that enhanced the rest schedule and improved access to hydration and shade were given before the 2018–2019 harvest (harvest 2). Actual work conditions during harvest 2 were then observed. Serum creatinine (SCr) was measured before and at end-harvest, and cross-harvest changes in estimated glomerular filtration rate (eGFR) and incident kidney injury (IKI, ie, SCr increase by ≥0.30 mg/dL or ≥1.5 times the baseline value) were compared between harvest 1 and harvest 2 for three jobs with different physical workloads using regression modelling. Workers who left during harvest were contacted at home, to address the healthy worker selection effect. Results: In burned cane cutters, mean cross-harvest eGFR decreased 6 mL/min/1.73 m 2 (95% CI 2 to 9 mL/min/1.73 m 2 ) less and IKI was 70% (95% CI 90% to 50%) lower in harvest 2 as compared with harvest 1 data. No such improvements were seen among seed cutters groups with less successful intervention implementation. Conclusion: Kidney injury risk was again elevated in workers with strenuous jobs. The results support further efforts to prevent kidney injury among sugarcane workers, and other heat-stressed workers, by improving access to water, rest and shade. The distinction between design and implementation of such interventions should be recognised.